2022
DOI: 10.1371/journal.pone.0267090
|View full text |Cite
|
Sign up to set email alerts
|

Genomic landscape of pathogenic mutation of APC, KRAS, TP53, PIK3CA, and MLH1 in Indonesian colorectal cancer

Abstract: Background Colorectal cancer (CRC) needs several mutations to occur in various genes, and can vary widely in different individuals; hence it is essential to be discovered in a specific population. Until recently, there has been no known study describing APC, TP53, PIK3CA, KRAS, and MLH1 of CRC in Indonesian population. This study describes the nature and location of mutation in CRC patients treated at three different hospitals in Jakarta. Methods This descriptive study was conducted on CRC patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…TP53, located on the short arm of human chromosome 17, is a tumor suppressor gene and the most common mutant gene in the human cancer cell [ 31 ]. In addition, TP53 mutations can be detected in 50–60% of human cancers, and some mutated proteins play a cancer-promoting role in tumors such as colon cancer, head and neck squamous cell carcinoma, and lung adenocarcinoma [ 32 , 33 , 34 ]. Thus, it is an important prognostic and predictive marker in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…TP53, located on the short arm of human chromosome 17, is a tumor suppressor gene and the most common mutant gene in the human cancer cell [ 31 ]. In addition, TP53 mutations can be detected in 50–60% of human cancers, and some mutated proteins play a cancer-promoting role in tumors such as colon cancer, head and neck squamous cell carcinoma, and lung adenocarcinoma [ 32 , 33 , 34 ]. Thus, it is an important prognostic and predictive marker in cancer.…”
Section: Discussionmentioning
confidence: 99%
“…These five missense mutations are the most commonly reported KRAS mutations and were present in 22 of 54 samples (40.7%) analyzed here. Ben Salah et al [71] reported a KRAS mutation rate of 55.7%, while Marbun et al [72] reported a rate of 64%. In other studies, either Gly12Asp [73,74] or Gly12Val [71,75] were the most common KRAS mutations.…”
Section: Kras Missense Mutationsmentioning
confidence: 99%
“…Our study reports the PIK3CA (exon 9 and 20) mutation frequency of 43.85%, which is lower compared to a previous study in other regions of Indonesia with smaller sample size, reporting 70.9% mutation [59]. An NGS based study on Indonesian patients with advanced CRC revealed that all patients (100%, n=22) harboring PIK3CA mutation, distinctively in exon 2, 5, 7, 8, 10, 19, and 21, in addition to commonly reported exon 9 and 20 [42]. Similar to our result, a meta-analysis of 44 studies enrolling 17,621 patients has reported that mutations of PIK3CA exon 9 and 20 were associated with MSI, KRAS mutation and right-sided colon [60].…”
Section: Discussionmentioning
confidence: 70%